Non-Immersive Virtual Reality Exercise Can Increase Exercise in Older Adults Living in the Community and in Long-Term Care: A Randomized Controlled Trial - Sheehy L; Bharadwaj L; Nissen KA; Estey JL (Clinical Interventions in Aging)
Lisa Sheehy,1 Lalita Bharadwaj,2 Kelsey Annie Nissen,2 Justine L Estey2 1Bruyère Health Research Institute, Ottawa, Ontario, Canada; 2Centre for Innovation and Research in Aging, Fredericton, New Brunswick, CanadaCorrespondence: Lisa Sheehy, Bruyère Health Research Institute, 43 Bruyère St, Ottawa, ON, K1N 5C8, Canada, Tel +01 613 562 6262 ext. 1593, Email lsheehy@bruyere.orgPurpose: To assess the impact of an 8-week non-immersive virtual reality exercise program for older adults on 1) balance, physical function, community integration and quality of life; 2) falls, emergency room visits, hospital and long-term care admissions; 3) quantity of exercise performed; and 4) acceptance of non-immersive virtual reality.Patients and Methods: This prospective, assessor-blinded, randomized controlled trial was carried out on two separate samples of older adults: those living in their own homes (“home-based”) and those living in long-term care (“facility-based”). Participants were randomized to non-immersive virtual reality or usual activity. Non-immersive virtual reality consisted of 20– 30 minutes of customized, gamified exercises for balance, stepping, strengthening, and aerobic conditioning, performed 3– 5x/week for 8 weeks. Outcomes were measured before the intervention, immediately after, and 1 month later. Physical testing and questionnaires addressed objective 1). Counts for objectives 2) and 3) were reported by the participants and retrieved from the non-immersive virtual reality platform. Logbooks and a short interview addressed objective 4).Results: Recruitment was substantially impacted by the COVID-19 pandemic. The facility-based sample had 31 participants; the home-based sample had 16. There were no statistically-significant benefits to non-immersive virtual reality in either sample for objective 1), although the facility-based non-immersive virtual reality group showed a clinically-significant improvement in functional walking. Effect sizes were small (≤ 0.16). No falls occurred during non-immersive virtual reality exercise. The facility-based non-immersive virtual reality group did an average of 14.1 sessions (average 20.1 minutes/session) and the home-based non-immersive virtual reality group did an average of 17.2 sessions (22.6 minutes/session). Participants enjoyed the non-immersive virtual reality, found it challenging and motivating and felt that it improved balance and walking. Most were interested to continue beyond the study.Conclusion: Non-immersive virtual reality for home-based and facility-based older adults is safe, enjoyable and feasible and may increase users’ weekly levels of physical activity leading to clinical benefits for functional walking in facility-based users.Trial Registration: ClinicalTrials.gov (NCT04083885; registered 2019– 09-06).Plain language summary: Regular exercise is so important for older adults. It improves strength, flexibility, endurance and balance, reduces the risk of falls, and increases independence. However, many older adults do not exercise, for a variety of reasons. We tested a fun and safe way for seniors to do a customized exercise program in their own home, using a non-immersive virtual reality platform called Jintronix, which turns exercise into games!We recruited older adults living in their own homes (home-based sample), and those living in long-term care (facility-based sample) to try the exercise program for 20-30 minutes, 3-5 times a week for 8 weeks. The exercises were customized to each participant by a therapist, who followed up weekly.A total of 47 participants were recruited. The 16 home-based participants did an average of 17 sessions (23 min/session) over the 8 weeks, and the 31 facility-based participants did an average of 14 sessions (20 min/session). The sessions were safe – no one fell or sustained significant injury while doing non-immersive virtual reality exercise. Participants enjoyed the program and found it challenging and motivating, and commented that it improved their balance and walking. Most participants wished to continue once the study was over.We have confirmed that non-immersive virtual reality exercise can engage older adults to exercise more, with the potential to improve their health and independence. This exercise option is ideal for older adults who find it difficult to leave their home or wish to exercise privately.Keywords: exergaming, older adults, healthy aging